Implikasi Globalisasi dan Penegakan Hukum Progresif di Indonesia - Dharma Setiawan Pagaralam (Universitas Bandar Lampung (UBL), 2011)
The implication of globalization toward Indonesia law order, most off all enter topass international agreement that ratified, influential towards law system, that isfrom aspect subtance with more law and regulation quantity that profess tounderstand liberal or neo-liberal; from structure aspect influences aparatur in decidewisdom inclined pro-state progress regardless of society condition, and from aspectcurtural influences manner looks at, attitude, and society behaviour inclined individualtowards obedience and cognizance right and law duty. Law enforcement in Indonesiais crisis, such crisis condition, can be sowed with institution loss authoritative,curropt apparatus and figured think positivistic analytic, low of legal cultural society,with legal culture doesn’t support, so that need a efforts approaches new progressive,by think holistik.